Effect of insecticidal fusion proteins containing spider toxins targeting sodium and calcium ion channels on pyrethroid‐resistant strains of peach‐potato aphid (Myzus persicae). Issue 7 (28th August 2014) - Yang, Sheng; Fitches, Elaine; Pyati, Prashant; Gatehouse, John A
Abstract BACKGROUND The recombinant fusion proteins Pl1a/GNA and Hv1a/GNA contain the spider venom peptides δ‐amaurobitoxin‐PI1a or ω‐hexatoxin‐Hv1a respectively, linked to snowdrop lectin (GNA). Pl1a targets receptor site 4 of insect voltage‐gated sodium channels (NaCh), while Hv1a targets voltage‐gated calcium channels. Insecticide‐resistant strains of peach‐potato aphid (Myzus persicae) contain mutations in NaCh. The pyrethroid‐resistant kdr (794J) and super‐kdr (UKO) strains contain mutations at residues L1014 and M918 in the channel α‐subunit respectively, while the kdr + super‐kdr strain (4824J), insensitive to pyrethroids, contains mutations at both L1014 and M918. RESULTS Pl1a/GNA and Hv1a/GNA fusion proteins have estimated LC50 values of 0.35 and 0.19 mg mL−1 when fed to wild‐type M. persicae. For insecticide‐resistant aphids, LC50 for the Pl1a/GNA fusion protein increased by 2–6‐fold, correlating with pyrethroid resistance (wild type < kdr < super‐kdr < kdr + super‐kdr strains). In contrast, LC50 for the Hv1a/GNA fusion protein showed limited correlation with pyrethroid resistance. CONCLUSION Mutations in the sodium channel in pyrethroid‐resistant aphids also protect against a fusion protein containing a sodium‐channel‐specific toxin, in spite of differences in ligand–channel interactions, but do not confer resistance to a fusion protein targeting calcium channels. The use of fusion proteins with differing targets could play a role in managing pesticide resistance. © 2014 Society of Chemical Industry